Initial organization and progressive expansion of the math-responsive brain network during the first school years - Théo Morfoisse; Séverine Becuwe; Marie Palu; Cassandra Potier-Watkins; Ghislaine Dehaene-Lambertz; Stanislas Dehaene (Proceedings of the National Academy of Sciences, 2026)
The neural mechanisms by which the developing brain acquires higher mathematical concepts from elementary intuitions remain poorly understood. Through a large-scale longitudinal functional MRI study of children from preschool through first and second grade, we tracked how neural responses to mathematical and nonmathematical statements change in the first 2 y of formal schooling, and we used these data to evaluate several theories of developmental change. Before school, when listening to math statements, children already engaged an adult-like cortical network, with partial specialization for geometry. Over the first 2 y of school, we observed an overall increase in math-related activation, a small recruitment of additional neural territory, reduced activation for facts that get better known, and a small overall increase in the dimensionality of representational space. fMRI responses to individual sentences suggest that these mechanisms, particularly in left inferior frontal gyrus and bilateral intraparietal sulcus, all contribute to children’s growing mastery of mathematical concepts.